Tilting Scripts: Incongruence as a Source of Humour in the Parodos of the Frogs - Szabó, Etelka (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The purpose of the following study is to decode the semantic layers of ancient Greek texts and scripts introducing the well-defined “General Theory of Verbal Humour”. Classical tragedies, the parodoi of the texts used by Aristophanes and the dialogues following them, are all formed according to a (more or less standardised) script. Via putting frogs on the stage, Aristophanes parodies the patterns of the chorus songs and agons in Greek tragedies. Although the setting – the River Styx – could not be more sublime, and the winner of the debate is Dionysus himself, his adversaries are “only” frogs. The Frog Song reveals that the unity of content and form is not to be broken up without serious damage to the effect, as their separation from each other results in the reverse of the original catharsis. This parody, however, does not only refer to the emptiness and anachronistic quality of certain forms, that is, it does not only ridicule the genre, but can also function as the continual self-correction of Aristotelian mimesis. Aristophanes’ parody of a parodos is a meticulously constructed text, a faithful image of the prototypical scripts functioning as source texts, and abundant in humorous effects. Parody is enjoyable in itself, however as any good parody works with the mechanisms creating the parent text; it can only appear comic if it really reveals the patterns underlying the original, and it can only reach its aim if these patterns really bring the original work of art to the recipient’s mind.